THE INFLUENCE OF THE DISRUPTION ERA IN THE CONCEPT OF LABOR RELATIONS IN THE HOSPITALITY INDUSTRY PERSPECTIVE OF EMPLOYMENT LAW - Milawati, Mami; Uwiyono, Aloysius (Sean Institute, 2022)
The disruption era, among others related to dynamics globalization and transformation of information technology that rapidly develop has changed the social and economic order, including changes in employment. This changes demands productivity and competitiveness of human resources as a prerequisite for Indonesian workers to play their role in the global economy. Flexible working relationships or labour flexibility is now the norm in the world of work worldwide. The government role includes improving quality of Indonesian workers to be productive and competitive, therefore direction of development policies in the manpower sector focuses on efforts to create widest job opportunities and increase protection of rights and welfare for workers, both at work until completion of the Employment Relations. Therefore, regulations are needed to be able to provide legal certainty, in order to answer the challenges and dynamics of manpower, especially on strategic issues regarding Work Relations which include implementation on Work Relations and protection regulation of workers therein.